A holistic interdisciplinary approach towards environmental justice and youth empowerment - Westhuizen, Marichen A. van der (HTS teologiese studies, 2021)
South African youth is described as marginalised and vulnerable because of, amongst others, high unemployment rates, a lack of access to opportunities and environmental degradation that threatens their and future generations’ well-being. Both social work and faith-based organisations place value on the empowerment of marginalised youth, as well as on the importance of participatory environmental initiatives. Practice guidelines to effectively empower youth in this regard are, however, lacking. This discussion was aimed at determining how environmental social work can take place in collaboration with faith-based organisations to contribute to both the empowerment of youth and environmental justice. A search of literature from 2010 onwards was conducted, focusing on the terms ‘sustainable development’, ‘marginalised youth’, ‘environmental and/or green social work’ and ‘faith-based organisations’. Central themes were identified through a thematic analysis. Four central themes were identified for youth empowerment through an interdisciplinary approach to contribute to environmental justice, namely environmental responsibility, attitude, knowledge and concern. It was concluded that the potential of an interdisciplinary environmental approach may be based on collaboration and an openness to include a renewed change orientation where disciplines work together across boundaries in multiple spaces to support environmental change and youth empowerment simultaneously.Contribution: The framework for collaborative initiatives may service as a guide to support marginalised youth to actively participate in social and environmental justice initiatives to contribute to their own and future generations’ well-being.